The future of economics : an islamic perspective - Chapra, M.Umer (United Kingdom : The Islamic Foundation, 2000)
Economics
2004-11-02
Keywords: Economics - Islamic perspective; Conventional economics; Islamic economics; Monetary policy; Public finance